The Geochemical Study of Oil-Oil and Oil-Source Rock Correlations in the Wushi Sag of the Beibu Gulf Basin, South China Sea - Wang, Yao-Ping; Zhan, Xin; Zhou, Xun; Gao, Yuan; Wang, Sibo; Xia, Jia; Song, Zhiguang (Frontiers in Earth Science, 2022)
Chemometrics has been widely used to cope with the problems of oil-oil and oil-source correlations because of its unique advantages in the comprehensive consideration of multiple parameters and the classification of samples or variables. In this paper, three chemometric methods, especially multidimensional scaling, were used to revisit the genetic oil family and the relationship between the crude oil and the source rock, because the oil source in the Wushi Sag, a significant petroliferous sag in the Beibu Gulf Basin of South China Sea, is still controversial. Two genetic families of crude oils, namely group A and group B, have been identified based on chemometric results. Group A oils are characterized by relatively higher Pr/Ph ratios and a high abundance of C27 ααα 20R steranes and C30-methylsteranes than those of group B oils, suggesting that this group of oils was deposited under a more oxic condition with more contribution of algae organic matter. Group A oils have been interpreted to be a mixture derived from the member 2 and member 3 of the Liushagang Formation (LS-2 and LS-3), whereas group B oils can be ascribed to the LS-2 member. The contribution of LS-3 mudstone member to the Wushi oils in previous studies may have been underestimated to some extent, which was inferred from the chemometric oil-source correlation results. The results of oil-source rock correlation may be used to guide future petroleum exploration activities with the incorporation of geological evidence. The spatial distribution of oil and gas reservoirs varies with burial depth. Considering the tectonic location, reservoir characteristic and the spatial distribution of group A and group B, we may infer that the reservoir in eastern Wushi Sag was mainly distributed in the deep of Liushagang Formation, whereas the reservoir in central Wushi Sag was likely located in shallow Liushagang Formation.